PENGARUH EMPOWERMENT, SELF-EFFICACY DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PEGAWAI NEGERI BADAN PENELITIAN DAN PENGEMBANGAN PROVINSI RIAU - Oktri, Oktri; Zulfadil, Zulfadil (Jurnal Tepak Manajemen Bisnis, 2019)
This study aims to analyze the influence of empowerment, self-efficacyand organizational commitment on job satisfaction and organizational citizenshipbehavior (OCB) of Civil Servants of the Research and Development Agency ofRiau Province.The population of the study was the Civil Servants of the Research andDevelopment Agency of Riau Province as many as 86 employees. Sampling in thisstudy using the census method, which according to this method all employees canbe examined. Data were collected by distributing questionnaires. The analyticalmethod used path analysis with the help of the SPSS program.The results of this study indicate that there was a positive and significantinfluence between empowerment, self-efficacy and commitment organizational tojob satisfaction and organizational citizenship behavior. However, in this studythe results showed that job satisfaction did not mediate intervening empowermenteffects, self-efficacy and organizational commitment to Organizational CitizenshipBehavior.